Physical principles in sensing and signaling : with an introduction to modeling in biology - Endres, Robert G. (Oxford University Press, 2013)
Although invisible to the bare eye, bacterial cells are large enough to make complex decisions. Cells are composed of thousands of different molecular species including DNA, proteins, and smaller molecules, allowing them to sense their environment, to process this information, and to respond accordingly. Such responses include expression of genes or the control of their movement. Despite these properties, a living cell exists in the physical world and follows its laws. Keeping thisin mind can help answer questions such as how cells work and why they implement solutions to problems the way they.